Two rare halophyte species: Aster tripolium L. and Plantago maritima L. on the Baltic coast in Poland – their resources, distribution and implications for conservation management - Lazarus, Magdalena; Wszałek-Rożek, Katarzyna (Biodiversity: Research and Conservation, 2016)
The paper presents the results of geobotanical studies on the distribution and resources of Aster tripolium L. and Plantago maritima L, two rare halophytes in Poland. The research was conducted in northern Poland, along the Baltic coast in 2013. The present distribution of the two species was compared with historical data and general trends of and threats to these two species were examined. In total, 33 sites of A. tripolium and 18 of P. maritima were found in the research area. The resources of both species have been perceptibly depleting during last 150 years, which is mostly due to human agencies (e.g. habitat devastation caused by growing urban areas and the change in management and/or habitat condition). In order to preserve both species, it may be necessary to start an ex situ conservation program.